2013
DOI: 10.1007/s13632-013-0081-9
|View full text |Cite
|
Sign up to set email alerts
|

Tribology of a Fe–Cr–B-Based Alloy Coating Fabricated by a Controlled Short-Circuit MIG Welding Process

Abstract: The aim of this study was to study the microstructure and tribology of a Fe-Cr-B-based alloy coating deposited by a controlled short-circuit metal inert gas welding process onto a 1020 carbon steel substrate with varying input energies. Microstructure analysis showed that the as-deposited alloy consisted of (Cr,Fe) 2 B particles embedded in a BCC solid solution matrix composed of Fe, Cr, Mn, and Si. The hardness of (Cr,Fe) 2 B particles was 24 GPa. When the input energy increased during welding process, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…AISI 1010 altlık malzemenin Rockwell B skalasında ölçülen sertlik değeri 63 HRB'dir. Bu sonuçların literatürde yapılan benzer sonuçlar ile uyum içerisinde olduğu tespit edilmiştir [32,[34][35][36]. Gerçekleştirilen Fe-Cr-B esaslı sert yüzey alaşımlama işlemi ile malzemelerin yüzey sertlik değerleri büyük oranda arttığı söylenebilir.…”
Section: Aşınma Ve Sertlik (Wear and Hardness)unclassified
“…AISI 1010 altlık malzemenin Rockwell B skalasında ölçülen sertlik değeri 63 HRB'dir. Bu sonuçların literatürde yapılan benzer sonuçlar ile uyum içerisinde olduğu tespit edilmiştir [32,[34][35][36]. Gerçekleştirilen Fe-Cr-B esaslı sert yüzey alaşımlama işlemi ile malzemelerin yüzey sertlik değerleri büyük oranda arttığı söylenebilir.…”
Section: Aşınma Ve Sertlik (Wear and Hardness)unclassified
“…Fe-Cr-B wear-resistant alloys have received extensive attention from material scientists all over the world [1][2][3]. Many investigations have found that the Fe-Cr-B alloy has high hardness, good wear resistance, excellent oxidation and corrosion resistance [4,5]. However, the Fe-Cr-B wear-resistance alloy has poor hardness and wear resistance at high temperature, which makes it difficult to satisfy the requirements of the rolling industry for the manufacture of rolls [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Among the past decades, researchers have manufactured Co-based coatings on the surface of steels utilising surface welding technologies such as TIG, MIG and MAG welding. [16][17][18] Coatings made by surface welding could achieve good properties and also have the advantage of low cost. However, the cladding materials were usually wire or electrodes in which the ceramic particles could not be added.…”
Section: Introductionmentioning
confidence: 99%